Pembaruan Hukum Keluarga Islam di Indonesia: Analisis Produk Hukum Mahkamah Agung tentang Hak-Hak Istri dan Anak Pasca Perceraian - Fauzi, Anwar (Peradaban Journal of Law and Society, 2025)
The implementation of post-divorce rights for wives and children in Indonesia continues to face significant challenges, marked by a persistent gap between legal provisions and practical enforcement, with limited court rulings that fully guarantee these rights. This article aims to analyze the reform of Islamic family law in Indonesia and to compare the substance of post-divorce rights as regulated in statutory legislation with those articulated through the legal instruments of the Supreme Court. Employing a normative-comparative approach, this study finds that the Supreme Court has substantially reformed legal norms concerning post-divorce rights through various instruments—including Supreme Court Regulations (PERMA) and Circular Letters (SEMA)—issued between 2017 and 2022. These reforms, which include stricter obligations for payment prior to the pronouncement of divorce (ikrar talak), provisions for non-custodial parental access, more equitable considerations of economic capacity in determining financial support, and the introduction of enforcement mechanisms such as asset seizures for child support, reflect the Supreme Court’s ijtihad in alignment with the principles of maqāṣid al-sharī‘ah as well as contemporary concerns of gender justice and human rights. This study contributes to mapping the dynamics and direction of Islamic family law reform in Indonesia, highlighting the strategic role of the Supreme Court in ensuring protection and legal certainty. Implementasi hak-hak istri dan anak pasca perceraian di Indonesia masih menghadapi tantangan serius, ditandai oleh kesenjangan antara ketentuan hukum dan praktik di lapangan, dengan minimnya putusan pengadilan yang menjamin pemenuhan hak-hak tersebut. Artikel ini bertujuan untuk menganalisis potret pembaruan hukum keluarga Islam di Indonesia dan membandingkan substansi hak-hak istri dan anak pasca perceraian dalam peraturan perundang-undangan dengan produk hukum Mahkamah Agung. Menggunakan pendekatan normatif-komparatif, studi ini menemukan bahwa Mahkamah Agung telah secara signifikan memperbarui kaidah hukum terkait hak-hak pasca perceraian melalui berbagai produk hukumnya (Peraturan Mahkamah Agung/PERMA dan Surat Edaran Mahkamah Agung/SEMA) sejak 2017 hingga 2022. Pembaruan ini, yang mencakup kewajiban pembayaran yang lebih tegas sebelum ikrar talak, hak akses orang tua non-hak asuh, pertimbangan kemampuan ekonomi yang lebih adil dalam penentuan nafkah, serta mekanisme jaminan pemenuhan hak (seperti sita jaminan untuk nafkah anak), merefleksikan ijtihad Mahkamah Agung yang selaras dengan prinsip maqasid al-syariah serta isu-isu keadilan gender dan hak asasi manusia. Penelitian ini berkontribusi dalam memetakan dinamika dan arah pembaruan hukum keluarga Islam di Indonesia, menyoroti peran strategis Mahkamah Agung dalam memberikan perlindungan dan kepastian hukum.